Income inequality and healthcare utilization of the older adults-based on a study in three provinces and six cities in China - Zhang Chi; Hai Lun; Jiaxin Ma; Yaping Zhou (Frontiers Media S.A., 2024)
PurposeThe objective of this study is to gain a more nuanced understanding of the specific impact of income inequality on the utilization of healthcare services for older adults. Additionally, the study aims to elucidate the moderating and mediating roles of public transfer income and psychological health in this context.MethodsA systematic examination of the impact of income inequality on healthcare utilization among older adults was conducted through field questionnaire surveys in six cities across three major geographical regions (West, Central, and East). The analysis employed baseline regression, as well as mediating and moderating effect tests.ResultsFirst, there is a negative relationship between income inequality and the use of therapeutic healthcare services (β1 = −0.484, P < 0.01) and preventive healthcare services (β2 = −0.576, P < 0.01) by older adults. This relationship is more pronounced in the low- and medium-income groups as well as in the western region. The mediating effect of psychological state is significant (β3 = −0.331, P < 0.05, β4 = −0.331, P < 0.05). Public transfer income plays a significant role in regulation. The moderating effect of public transfer income on therapeutic services was more significant in low-income groups (β5 = 0.821, P < 0.01). The moderating effect of public transfer income on preventive services was more significant in middle-income groups (β6 = 0.833, P < 0.01).ConclusionThe study clearly demonstrates a significant negative correlation between income inequality and the utilization of healthcare services by older adults. Furthermore, the study reveals that this relationship is particularly pronounced among older adults in low- and medium-income and Western regions. This detailed analysis of regional and income level heterogeneity is of particular value in this field of research. Secondly, this study attempts to integrate the two pivotal dimensions of public transfer income and psychological state for the first time, elucidating their moderating and mediating roles in this relationship. The findings indicate that public transfer income serves as a moderating factor, exerting a notable "reordering effect" on income inequality and resulting in a "deprivation effect." Such factors may impede the utilization of medical services, potentially influencing the psychological state of older adults.